PENGARUH PERANAN KELOMPOK WANITA TANI TERHADAP PELAKSANAAN PROGRAM P2KP DI KABUPATEN TEMANGGUNG - , FINSA ANINDITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aimed to determine the role of women farmer group on P2KP program implentation and factors that influence it, and determine the effect of the role of women farmer group and other factors on the implementation of the program P2KP. The basic method used in this research was analytical descriptive with survey techniques. Two sample subdistricts and four women farmer groups were selected purposively. From each women farmer group sample was taken 15 members by random sampling. Data was analyzed by frequency distribution tables and multiple linear regression analysis. The research results showed that the role of women farmer group in the program P2KP and the implementation of P2KP program in the high category. Factor affecting positively the role of women farmer group was motivation. Age, education, attitudes, the role of extension, and the role of group leader didnât affect the role of women farmer group. Factors affecting the implementation of the P2KP program were attitude, age, motivation, role of counselor, group leader role, and the role of women farmer group